The Role of the Hidden Curriculum in the Secondary Education Revolution in the United States - Putra, M. Ridha Rahmat; Ngardi, Valensius; DeLuca, Christopher; Rickey, Nathan; Hui, Sammy King Fai (Journal of Educational Management and Strategy, 2024)
Secondary education in the United States is undergoing significant changes in response to the technological and economic developments of the Industrial Revolution 5.0. In facing these challenges, the role of hidden curriculum becomes crucial in preparing students for the increasingly interconnected and automated workforce. Hidden curriculum, which includes values, attitudes, and social skills that are not explicitly taught, has a significant impact on shaping students' character and interpersonal skills. This study aims to examine how hidden curriculum in U.S. secondary education plays a role in preparing the younger generation for the challenges of the industry, particularly in the development of social skills, creativity, work ethics, and adaptability. The research method used is a qualitative approach, through literature analysis and interviews with teachers and students, to explore the implementation and impact of hidden curriculum in the context of secondary education. The findings indicate that while formal curricula often focus on technical skills, hidden curriculum plays an equally important role in developing the skills necessary for success in the Industrial Revolution 5.0. This study suggests that more attention should be given to the integration of social values and interpersonal skills into the secondary education curriculum, as well as the importance of teacher training to optimize the role of hidden curriculum in preparing students for the ever-evolving global challenges.